NEUROPROTECTIVE EVALUATION OF LEAF EXTRACT OF DALBERGIA SISSOO IN 3-NITROPROPIONIC ACID INDUCED NEUROTOXICITY IN RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
This research was performed to characterize the neuroprotective effect of ethanolic extract of Dalbergia sissoo leaves in 3-Nitropropionic acid induced neurotoxic rats. The ethanolic extract of Dalbergia sissoo leaves was administered orally at different doses (300 and 600 mg/kg) to neurotoxic rats. During treatment psychopharmacological parameters were recorded, 24 hours after experiment antioxidant profiles from brain isolate were estimated and histopathology of brain was performed. The ethanolic extract significantly attenuated behavioral alterations, oxidative damage, mitochondrial dysfunction, and striatal/hippocampus damage in 3-Nitropropionic acid treated rats. These results suggest that ethanolic extract of Dalbergia sissoo leaves may have potential therapeutic value in the treatment of some neurological disorders, probably by its anti-inflammatory, antioxidant and estrogenic properties.